SIRT6 overexpression retards renal interstitial fibrosis through targeting HIPK2 in chronic kidney disease - Li, Xiaoxue; Li, Wenxin; Zhang, Zhengzhipeng; Wang, Weidong; Huang, Hui (Frontiers in Pharmacology, 2022)
Introduction: Renal interstitial fibrosis is a common pathophysiological change in the chronic kidney disease (CKD). Nicotinamide adenine dinucleotide (NAD)-dependent deacetylase sirtuin 6 (SIRT6) is demonstrated to protect against kidney injury. Vitamin B3 is the mostly used form of NAD precursors. However, the role of SIRT6 overexpression in renal interstitial fibrosis of CKD and the association between dietary vitamin B3 intake and renal function remains to be elucidated. Methods: Wild-type (WT) and SIRT6-transgene (SIRT6-Tg) mice were given with high-adenine diets to establish CKD model. HK2 cells were exposed to transforming growth factor β1 (TGF-β1) in vitro to explore related mechanism. Population data from Multi-Ethnic Study of Atherosclerosis (MESA) was used to examine the association between dietary vitamin B3 intake and renal function decline. Results: Compared to WT mice, SIRT6-Tg mice exhibited alleviated renal interstitial fibrosis as evidenced by reduced collagen deposit, collagen I and α-smooth muscle actin expression. Renal function was also improved in SIRT6-Tg mice. Homeodomain interacting protein kinase 2 (HIPK2) was induced during the fibrogenesis in CKD, while HIPK2 was downregulated after SIRT6 overexpression. Further assay in vitro confirmed that SIRT6 depletion exacerbated epithelial-to-mesenchymal transition of HK2 cells, which might be linked with HIPK2 upregulation. HIPK2 was inhibited by SIRT6 in the post-transcriptional level. Population study indicated that higher dietary vitamin B3 intake was independently correlated with a lower risk of estimate glomerular filtration rate decline in those ≥65 years old during follow-up. Conclusion: SIRT6/HIPK2 axis serves as a promising target of renal interstitial fibrosis in CKD. Dietary vitamin B3 intake is beneficial for renal function in the old people.